Environment Associated with Deep Moist Convection under SALLJ Conditions: A Case Study - Borque, Paloma Celina (2010)
The present work focuses on the study of the environmental conditions preceding the development of a group of subtropical mesoscale convective systems over central and northern Argentina on 6 ? 7 February 2003, this situation took place during the South American Low Level Jet Experiment (SALLJEX). This period was characterized by an extreme South American Low Level Jet (SALLJ) event that occurred east of the Andes. The entire studied episode was dominated by the presence of a very unstable air mass over northern Argentina and a frontal zone near 40 ºS. The SALLJ generated an important destabilization of the atmosphere due to the strong humidity and differential temperature advection. Orography provided an extra lifting motion to the configuration of the regional wind field, efficient in forcing the initiation of convection. Once convection developed it moved and regenerated in regions where convective instability was horizontally homogeneous and stronger.